How Are Research Trends on Reading Activity in Science Learning? Tracking from 2000 to 2019 on Selected Journal - Siswanto, Siswanto; Hartono, Hartono; Subali, Bambang; Masturi, Masturi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
The number of studies and researchers in the science education field is constantly increasing from year to year. It makes research about article review very important because it helps researchers determine the research orientation. In this study, a research review was conducted on reading activities in science learning. There have been several studies on tracking research trends in science education in recent years, but there has not been any detailed discussion about reading activities in science learning. Therefore, it is necessary to know the development trends of research on reading activities in science learning. In this study, we analyze 74 articles published from 2000-2019 using the open-coding system. By using a search engine, it is done by entering one keyword or a combination of several keywords, include reading, a variety of ”reading and text," ”reading and science text," ”reading and textbook," ”reading, text, and science." The results showed that there were still many empty things that the researchers had not studied. The United States dominates the average researcher with a primary focus on reading comprehension. In terms of participants, research is dominated by involving students in schools (although the numbers are still small), with the variables studied are dominated by reading comprehension. This research can help researchers find gaps in research that have not been carried out related to reading activities in science learning.